Tracking-Free Determination of Single-Cell Displacements and Division Rates in Confluent Monolayers - Giavazzi, Fabio; Malinverno, Chiara; Scita, Giorgio; Cerbino, Roberto (Frontiers in Physics, 2018)
A biological tissue is an ensemble of soft cells in close physical contact. Events such as cell-shape changes and, more rarely, cell-divisions and apoptosis continuously occur in a tissue, whose collective behavior is set by the cumulative occurrence of such events. In this complex environment, quantifying the single-cell dynamics is key to extract quantitative information to be used to capture the fundamental ingredients of this collective tissue dynamics for validating the predictions of models and numerical simulations. However, tracking the motion of each cell in a dense assembly, even in controlled in vitro settings, is a demanding task, because of a combination of different factors, such as poor image quality, cell shape variability and cell deformability. Here we show that Differential Dynamic Microscopy (DDM), an approach that provides a characterization of the sample structure and dynamics at various spatial frequencies (wave-vectors), can be used successfully to extract quantitative information about a confluent monolayer of Madin-Darby Canine Kidney (MDCK) epithelial cells. In particular, combining structural and dynamical information obtained at different wave-vectors, we show that DDM can provide the single-cell mean squared displacement and the cell division rate at various stages during the temporal evolution of the monolayer. In contrast with tracking algorithms, which require expert supervision and a considerate choice of the analysis parameters, DDM analysis can be run in an automated fashion and yields an unbiased quantification of the dynamic processes under scrutiny, thus providing a powerful means to probe the single-cell dynamics within dense cell collectives.